Novel Nafion/Graphitic Carbon Nitride Nanosheets Composite Membrane for Steam Electrolysis at 110 °C - Taipu Chen; Bo Lv; Shucheng Sun; Jinkai Hao; Zhigang Shao (Membranes, 2023)
Hydrogen is expected to have an important role in future energy systems; however, further research is required to ensure the commercial viability of hydrogen generation. Proton exchange membrane steam electrolysis above 100 °C has attracted significant research interest owing to its high electrolytic efficiency and the potential to reduce the use of electrical energy through waste heat utilization. This study developed a novel composite membrane fabricated from graphitic carbon nitride (g-C3N4) and Nafion and applied it to steam electrolysis with excellent results. g-C3N4 is uniformly dispersed among the non−homogeneous functionalized particles of the polymer, and it improves the thermostability of the membranes. The amino and imino active sites on the nanosheet surface enhance the proton conductivity. In ultrapure water at 90 °C, the proton conductivity of the Nafion/0.4 wt.% g-C3N4 membrane is 287.71 mS cm−1. Above 100 °C, the modified membranes still exhibit high conductivity, and no sudden decreases in conductivity were observed. The Nafion/g-C3N4 membranes exhibit excellent performance when utilized as a steam electrolyzer. Compared with that of previous studies, this approach achieves better electrolytic behavior with a relatively low catalyst loading. Steam electrolysis using a Nafion/0.4 wt.% g-C3N4 membranes achieves a current density of 2260 mA cm−2 at 2 V, which is approximately 69% higher than the current density achieved using pure Nafion membranes under the same conditions.